Perlukah Gaji PNS Naik? (Studi Kasus Provinsi Kalimantan Tengah) - Agustinus Sulistyo (Pusjar SKPP Lembaga Administrasi Negara, 2008)
Many people said that government apparatus doesn’t get enough salary, so that it needs to be increased. But on the other side, people always get interested and very enthusiastic about the recruitment held by the government. How could this happen, with the small amount of money that they may get, why do people still interest to be the government apparatus? From the research that was conducted in Central Kalimantan, especially in Palangka Raya and Kapuas regency, we found out that the take home pay that government apparatus get is actually even much bigger than that is got by the private sector employee (can be seen from the UMP of Central Kalimantan province). By its nominal, government apparatus’ salary/income per month is actually high above the UMP. But the problem is, whether with the adequate salary they get, it will improve the work-performance of the government apparatus. Keywords : Public servant of civil, salary, take home pay, Center Borneo